A case-control study of medium-term exposure to ambient nitrogen dioxide pollution and hospitalization for stroke - Johnson, Julie YM (BioMed Central, 2013)
BACKGROUND: There are several plausible mechanisms whereby either short or long term exposure to pollution can increase the risk of stroke. Over the last decade, several studies have reported associations between short-term (day-to-day) increases in ambient air pollution and stroke. The findings from a smaller number of studies that have looked at long-term exposure to air pollution and stroke have been mixed. Most of these epidemiological studies have assigned exposure to air pollution based on place of residence, but these assignments are typically based on relatively coarse spatial resolutions. To date, few studies have evaluated medium-term exposures (i.e, exposures over the past season or year). To address this research gap, we evaluated associations between highly spatially resolved estimates of ambient nitrogen dioxide (NO(2)), a marker of traffic pollution, and emergency department visits for stroke in Edmonton, Canada. METHODS: This was a case-control study with cases defined as those who presented to an Edmonton area hospital emergency department between 2007 and 2009 with an acute ischemic stroke, hemorrhagic stroke, or transient ischemic attack. Controls were patients who presented to the same emergency departments for lacerations, sprains, or strains. A land-use regression model provided estimates of NO(2) that were assigned to the place of residence. Logistic regression methods were used to estimate odds ratios for stroke in relation to an increase in the interquartile range of NO(2) (5 ppb), adjusted for age, sex, meteorological variables, and neighborhood effects. RESULTS: The study included 4,696 stroke (cases) and 37,723 injury patients (controls). For all strokes combined, there was no association with NO(2.) Namely, the odds ratio associated with an interquartile increase in NO(2) was 1.01 (95% confidence interval CI: 0.94-1.08). No associations were evident for any of the stroke subtypes examined. CONCLUSION: When combined with our earlier work in Edmonton, our findings suggest that day-to-day fluctuations in air pollution increase the risk of ischemic stroke during the summer season, while medium term exposures are unrelated to stroke risk. The findings for medium term exposure should be interpreted cautiously due to limited individual-level risk factor data.